If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 1 = x + 2 + 24 Reorder the terms: 1 + x + x = x + 2 + 24 Combine like terms: x + x = 2x 1 + 2x = x + 2 + 24 Reorder the terms: 1 + 2x = 2 + 24 + x Combine like terms: 2 + 24 = 26 1 + 2x = 26 + x Solving 1 + 2x = 26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + 2x + -1x = 26 + x + -1x Combine like terms: 2x + -1x = 1x 1 + 1x = 26 + x + -1x Combine like terms: x + -1x = 0 1 + 1x = 26 + 0 1 + 1x = 26 Add '-1' to each side of the equation. 1 + -1 + 1x = 26 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = 26 + -1 1x = 26 + -1 Combine like terms: 26 + -1 = 25 1x = 25 Divide each side by '1'. x = 25 Simplifying x = 25
| y=x^2+8x-11 | | 35/8x12/15 | | -1.2r=6.0 | | x^2+8x-11=y | | 4=2y+105 | | 4=2y+70 | | -12r=6.0 | | 4=2y+35 | | 0=81+9y-7x | | -2(4y-7)-2(5y-9)-7y= | | 2x-8y-7x+5y= | | 0=81+9-7x | | 11-2(x+3)=2(1+x) | | P-5=7 | | 7(-w+5)+3(5w+2)=-w+3-3w | | (9x+7)-(7x-5)= | | 37.5q=-.50 | | -3(f-8)=32 | | 2x+5=-7x-13 | | 4(x+2)+8=2(4X-5)-14 | | 4(z-4)+4z-4= | | 7x-4+36=4x+47 | | 2(n+1)=5n-7 | | 0.2(b+3)+0.8b=-4.4 | | -27+15-22z=31 | | -1=-3r | | -4y+4=15 | | 3(5z-3)-2(z-9)= | | -4y+4=10 | | Uk+uz=x | | 29=b/-4+5 | | -65=24 |